The Effectiveness of Song Translation In Increasing Vocabulary To Develop Speaking Skills At SDN 1 Paciran - Fikri, Shofil; Al-Furqaan, Dimas Luqman (UIN Maulana Malik Ibrahim Malang, 2023)
Translation theory is all choices and decisions based on the experiences of each translator, which are subjective and result from a training process. So, in this study the authors aimed to test the effectiveness of the song translation method in increasing vocabulary to develop speaking skills in students of SDN 1 Paciran. This research is included in the type of quantitative research. And based on data collection techniques, this research is classified as experimental research, namely pre-experimental design by comparing one group pre-test and post-test. The song used is the song Los Dol Deny Cak Nan whose lyrics have been translated into Arabic. The data obtained were then analyzed using quantitative descriptive techniques with the help of IBM SPSS Statistics 26, so that researchers could find out how much influence the translation of songs had with the t-test. The results of this study indicate that translating songs in increasing vocabulary is very effective for developing the speaking skills of SDN 1 Paciran students, this is evidenced by the results of the paired sample test where sig. (2-tailed) shows the number 0.002.